Indoor location systems in emergency scenarios - A Survey - Bastos, Arivan; Vieira, Vaninha; Jr, Antonio (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2015: Anais do XI Simpósio Brasileiro de Sistemas de InformaçãoDO - 10.5753/sbsi.2015.5824, 2015)
Indoor location data are critical in emergency situations. Command centers need to monitor their operational forces. Rescuers need to find potential victims to carry proper care and the building’s occupants need to find the way for fast evacuation. Despite the growing body of research in indoor location, no technique is considered appropriate for different situations. Furthermore, few studies have analyzed the applicability of these techniques in an emergency setting, which has particular characteristics. This survey reviews works in indoor location applied to emergency scenarios, analyzing their applicability in relation to existing requirements in these types of situations.